2013
DOI: 10.1097/sap.0b013e31826af01a
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Transplantation of Adipose-Derived Stem Cells Enhances Skin Graft Survival and Wound Healing in Diabetic Rats

Abstract: These findings suggest that autologous ASC transplantation can enhance skin graft survival in diabetic rats through differentiation, vasculogenesis, and secretion of growth factors such as VEGF and TGF-β3. This might represent a novel therapeutic approach in skin graft surgery for diabetic wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 37 publications
3
52
0
Order By: Relevance
“…PHBV scaffold maintained 39 the wound moisture and demonstrated enough mechanical properties to withstand wound contraction. 40 Also, exudate and inflammatory cell infiltration enhanced the degradation of the structure, and thus heal- 41 ing progression. After 28 days all the wounds were closed and the PHBV scaffold was completely 42 degraded.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…PHBV scaffold maintained 39 the wound moisture and demonstrated enough mechanical properties to withstand wound contraction. 40 Also, exudate and inflammatory cell infiltration enhanced the degradation of the structure, and thus heal- 41 ing progression. After 28 days all the wounds were closed and the PHBV scaffold was completely 42 degraded.…”
mentioning
confidence: 98%
“…Overexpression of TGF-b1 results in excessive fibroblast 516 migration and myofibroblast differentiation, and therefore on the 517 deposition of a highly organized ECM over-accumulation and scar 518 formation[46,47]. On the other side, TGF-b3 inhibits scarring by519 promoting normal collagen organization[41,48]. For instance, the 520 fetal skin can heal without scars and this phenomenon is associ-521 ated with a decrease in TGF-b1 and TGF-b2 expression, accompa-522 nied by increased or prolonged TGF-b3 expression[48,49].Interestingly, the presence of PHBV scaffold reduced the gene 524 expression of TGF-b1 and the combination with ASCs also 525 increased TGF-b3 gene expression.…”
mentioning
confidence: 99%
“…Autologous ADSCs transplantation could enhance skin graft survival in diabetic rats through differentiation, vasculogenesis, and secretion of growth factors, such as VEGF and TGF-β3. This might represent a novel therapeutic approach in skin graft surgery for diabetic wounds [48] . MSCs combined with plastic surgery or skin graft therapy may be a promising therapeutic approach for improving radiation-induced skin and muscle damages [49] .…”
Section: Necrosismentioning
confidence: 99%
“…Studies have been done in rats comparing qualitatively peritoneal and inguinal region tissues 19 Studies with models of grafts 26 , and flaps 27 using the inguinal region ADSC showed increased viability of the necrotic area, however the route of administration of ADSC was subcutaneously. In the present study, the route of administration was intravenous, finding similar results to those mentioned, which…”
Section: Discussionmentioning
confidence: 99%